Impact of Aqueous Neem Leave Extract on Erythromycin Induced Hepatotoxicity - Jamshed, Nausheen; Raza, Iffat; Rasheed, Aqiba; Jamshed, Naureen; Akhtar, Lubna; Rashid, Nadia (Pakistan Armed Forces Medical Journal, 2022)
Objective: To examine the protective effect of aqueous neem leaves extract against damage induced by erythromycin on liver enzyme alkaline phosphatase. Study Design: Laboratory-based experimental study. Place and Duration of Study: Anatomy Department, Baqai Medical University, Karachi Pakistan, from Mar to Jun 2018. Methodology: Eighty male albino wistar rats were taken and were divided randomly into 4 groups. Group-A served as a control group with no drug given. Group-B animals received the drug erythromycin 100 mg/kg body weight orally through gastric lavage. Group-C animals received erythromycin 100 mg/kg body weight and neem leaves extract in a dose of 500 mg/kg body weight orally through gastric lavage. Group-D received only neem extract at the dose of 500 mg/kg body weight orally. After 14 days, blood samples were collected via cardiac puncture and sent to laboratory for the investigation of alkaline phosphatase enzyme. Results: The alkaline phosphatase enzyme levels of group-B (Erythromycin treated group) were found to be 176.98 ± 10.53 IU/L. When treated with aqueous neem leaves extract the alkaline phosphatase levels decreased to 150.10 ± 2.28 IU/L seen in group-C. The comparisons of group-B and group-C showed statistically significant (p<0.01), showing protective effect of aqueous neem leaves on hepatocytes. Conclusion: Aqueous neem extract showed protective effect on erythromycin induced hepatic damage.